A broadly adaptable protocol for isolating Kupffer cells from non-model species: application to Mastomys natalensis and its susceptibility to Old World mammarenaviruses - Corrales, Nicolas; Hansen-Kant, Katharina; Lander, Angelika; Prescott, Joseph B. (Frontiers in Immunology, 2025)
BackgroundKupffer cells are specialized, liver-resident macrophages that play central roles in hepatic homeostasis, immune surveillance and pathogen clearance. While well-studied in laboratory mice and rats, methods for isolating and studying Kupffer cells from non-model species remain scarce, limiting research in ecologically and zoonotically relevant hosts such as the Natal multimammate mouse (Mastomys natalensis), the natural reservoir of Lassa virus (LASV).Methodology and principal findingsWe developed and validated an optimized Kupffer cell isolation protocol adaptable to non-model rodents, relying on mechanical and enzymatic liver dissociation, non-parenchymal cell enrichment by Percoll gradient and selection by adherence. Critical parameters affecting yield and viability included maintaining all perfusion and digestion steps at 37 °C, limiting enzymatic digestion to ≤15min and avoiding aggressive mechanical disruption. Under optimized conditions, yields averaged 2.55 ± 1.13 × 105 viable Kupffer cells per gram of liver (≈80% viability). Isolated cells displayed macrophage-like morphology, expressed a Kupffer cell marker profile (CD11b+/Iba1+/MHC-II+/CD80+) and demonstrated phagocytic and pinocytic activity. As proof-of-concept, Kupffer cells were infected in vitro with LASV or Mopeia virus (MOPV). Both Mammarenaviruses successfully infected Kupffer cells, but infection kinetics differed; LASV persisted at stable levels without cytopathic effect, whereas MOPV replication declined over time, suggesting virus-specific control mechanisms.Conclusions and significanceThis protocol provides a robust, reproducible, and species-flexible method for isolating viable Kupffer cells from non-model rodents without requiring species-specific reagents. It enables functional, phenotypic, and virological studies in primary hepatic macrophages from M. natalensis and can be adapted to other wildlife reservoirs, supporting comparative immunology, zoonotic disease ecology, and host–pathogen interaction research in under-characterized species.